Objective Fictions Philosophy, Psychoanalysis, Marxism. - Johnston, Adrian (Edinburgh University Press, 2022)
This collection rethinks the relationship between objectivity and fiction beyond the realism-nominalism divide through a series of 'objective fictions', such as fetishes, semblances, lies, rumours, sophistry, fantasies and conspiracy theories. The contributors include Slavoj Žižek, Mladen Dolar, Frank Ruda and Samo Tomsič.